THE INEXTINGUISHABLE LIGHT ILLUMINATING THE CULTURE OF READING IS A PERSON'S LIFE PATH (Scientific journal of the Fergana State University, 2024)
The article talks about improving reading skills and culture. Auxiliary concepts: reading, family, book, reading culture The article discusses the development of reading skills and culture.